Self-Organization in Bipolar Disorder: Replication of Compartmentalization and Self-Complexity - Alatiq, Y; Crane, C; Williams, J; Goodwin, G (2010)
Remitted bipolar patients were compared to remitted unipolar patients and healthy controls on a self concept task assessing degree of self- compartmentalization (clustering of self-aspects based on valence) and self-complexity (the degree of relatedness versus differentiation across self-aspects). Similar to the findings of Taylor et al. (Cognitive Therapy and Research, 31(1), 83-96, 2007) the bipolar and unipolar groups showed higher levels of self compartmentalization than healthy controls. No differences were found on the self complexity measure. © 2010 Springer Science+Business Media, LLC.